The consequences of consolidating the votes of countries from Europe in the IMF’s Executive Board - Grujić, Miloš; Popović, Dejan (Anali Ekonomskog fakulteta u Subotici, 2020)
A few years ago, the expert public was discussing the consequences of consolidating the EU countries’ representation in the IMF’s Executive Board. The main idea was that EU members should be split into two constituencies. - the first one with members of the eurozone and the other a members outside the eurozone. The subject of this paper is to analyse the voting power in the Executive Committee of the International Monetary Fund using the Penrose-Banzhaf Index (PBI) and the Koleman’s Index (CI). The aim of the paper is to express the power of voting and the possibility of blocking certain decisions in relation to the position in the constituency. We will also take a look at the characteristics of the official missions of the IMF in order to determine the importance of the results and recommendations arising from the visit of the IMF team to the country.